Social improvement - Bishoff, R. W. (My University, 1897)
Introduction: From the earliest history of society we find a tendency for men to band themselves together for the protection of themselves and their families; and these primitive forms of society have grown up and sustained simply because they increased the efficiency of man as a feeding and fighting animal; just as it did that of the wolf, the bear, and other animals. Society has now grown to be for man the indispensable guarantee not only of nutrition and protection, but of the opportunity to conceive and attain a thousand varieties of more refined satisfaction. Thus we find society starting from the union of a few families who worked together for mutual benefit, and who have grown, and conquered every other form of life until today man stands far in advance of all other beings. But from the beginning we find certain principles and responsibilities which society has been forced to respect. These principles are not arbitrary they are not a matter merely conventional, born of compact, or molded by individual or popular caprice. Social life may be a Proteus in its form. It may wrap itself in the furs of the savage or the silks of the civilized man; it may breathe amid splendid palaces or be half stifled in caverns, but the principles that verify and sustain it are invariably the same. For the interests of a common wealth are paramount to all private interests, and a common responsibility is the mutual bond that unites its members together. The very idea of social life implies restraint of private impulses.
Citation: Bishoff, R. W. Social improvement. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Social; Improvement; Society; Sociology; Theses; Manuscripts (documents)